2020
DOI: 10.1002/ajhb.23448
|View full text |Cite
|
Sign up to set email alerts
|

The associations between digit ratio, aerobic fitness, physical skills, and overall physical fitness of elite youth distance runners

Abstract: Objective Lower digit ratios between the lengths of fingers 2 (2D) and 4 (4D) (2D:4D) are associated with superior distance running and athletic performance. We examined relationships between 2D:4D, aerobic fitness, physical skills, and overall physical fitness of elite adolescent boy and girl distance runners. Methods Subjects were top five finishers for their sex and age in 10 or more races of 10 km or longer in Michigan in 1981. We calculated 2D:4D of 15 girls and 11 boys from radiographs. Subject peak O2 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 55 publications
1
14
0
2
Order By: Relevance
“…The obtained results were in concordance with our hypothesis, where was predicted that players with low right and left hand 2D:4D would have high muscular strength performance. These results are in line with the findings of previous studies, that analyzed the relationship between athletic performance and digit ratio of adolescents [ 33 , 34 , 55 ], which have reported a negative correlate between digit ratio, aerobic fitness and physical skills in teenage boys and girls distance runners, or who reported a negative correlate between digit ratio and VO 2max in adolescents involved in different sports (soccer, squash, table tennis, and athletics), or even a moderate negative correlate between digit ratio and muscular strength found in adolescents. The results of the present study revealed insights to the coaches implement into the training process, especially in the soccer context, and could be important to optimize the performance of their athletes.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The obtained results were in concordance with our hypothesis, where was predicted that players with low right and left hand 2D:4D would have high muscular strength performance. These results are in line with the findings of previous studies, that analyzed the relationship between athletic performance and digit ratio of adolescents [ 33 , 34 , 55 ], which have reported a negative correlate between digit ratio, aerobic fitness and physical skills in teenage boys and girls distance runners, or who reported a negative correlate between digit ratio and VO 2max in adolescents involved in different sports (soccer, squash, table tennis, and athletics), or even a moderate negative correlate between digit ratio and muscular strength found in adolescents. The results of the present study revealed insights to the coaches implement into the training process, especially in the soccer context, and could be important to optimize the performance of their athletes.…”
Section: Discussionsupporting
confidence: 93%
“…Previous studies have reported high to very high correlations in fitness parameters with training load, as well as 2D:4D ratio with the aforementioned in youth athletes [ 19 , 31 , 34 , 37 ]. Therefore, the results were analyzed to obtain a sample size with at least 90% power.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The mechanisms by which these outcomes occur include activation of signaling pathways which promote mobilization of energy stores ( Sato et al, 2008 ; Mitsuhashi et al, 2016 ), modulation of neuromotor units ( Bonifazi et al, 2004 ), the accumulation of protein for muscle “growth” via mTor ( Basualto-Alarcon et al, 2013 ), and increased motivation ( Smith et al, 2013 ; Cook et al, 2021 ). Therefore, given the role testosterone can play when it comes to human behavior and performance, the mechanisms by which it works, and that prenatal testosterone exposure may influence testosterone responsiveness later in life, it is unsurprising to see that right 2D:4D has been shown to be predictive of social and competitive behaviors ( Kilduff et al, 2013a , b ; Crewther et al, 2015a ; Nepomuceno et al, 2016 ), sporting performance (including in international Rugby union, distance running, skiing, and sumo wrestling; Manning, 2002 , Manning et al, 2007 , 2014 ; Tamiya et al, 2012 ; Kilduff et al, 2013a ; Lombardo and Otieno, 2020 ), musical ability ( Sluming and Manning, 2000 ), risk taking behaviors ( Coates et al, 2009 ; Massimino et al, 2019 ), and academic performance ( Coco et al, 2011 ; Tektas et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Among highly skilled elite performers, it appears that striving for excellence is associated with a combination of physical and psychological factors [ 1 , 2 ]. Specifically, there is some evidence that individuals exposed prenatally to higher testosterone and lower estrogen concentrations might have a better physical performance as children [ 2 , 3 , 4 ], adolescents [ 5 , 6 ] (but see also [ 7 ] for opposite results), and adults [ 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 ]. Given this background, the following theoretical foundations and hypotheses were examined.…”
Section: Introductionmentioning
confidence: 99%